An Ambiguous Meaning Uttered by Characters Found in “My Lecturer My Husband Movie Season 2” - Nuryanti, Dewi; Sa’diah, Siti Nurhalimatus (ESENSI LINGUA, 2024)
This research aims to find out the reasons of characters uttering some ambiguous words, phrases, or sentences in the movie and to describe the meaning of ambiguous words uttered by characters. This research will also provide some ambiguous characteristic information that appears more often in the movie. The method used for this research is descriptive qualitative and the writers use theory by Crystal (2008). The data audio-visual data taken from the part of the conversation of the movie. The research obtained nine data contained the ambiguous word, phrases, or sentences. They are lexical and structural ambiguity. Lexical ambiguity is a characteristic that often appears in this movie. There are eight data using ambiguous lexical characteristics, while there is one data that uses ambiguous structural.